2020
DOI: 10.1186/s13287-020-01783-8
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo cultivated oral mucosal epithelial cell transplantation for limbal stem cell deficiency: a review

Abstract: Destruction or dysfunction of limbal epithelial stem cells (LESCs) leads to unilateral or bilateral limbal stem cell deficiency (LSCD). Fifteen years have passed since the first transplantation of ex vivo cultivated oral mucosal epithelial cells (COMET) in humans in 2004, which represents the first use of a cultured non-limbal autologous cell type to treat bilateral LSCD. This review summarizes clinical outcomes from COMET studies published from 2004 to 2019 and reviews results with emphasis on the culture met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 66 publications
0
38
0
1
Order By: Relevance
“…These procedures were named "cultivated oral mucosa epithelial transplantation" (COMET) and "cultivated autologous oral mucosal epithelial cell sheet" (CAOMECS) (Burillon et al, 2012), and they have been widely used in the last 20 years in at least 27 published clinical studies (Attico et al, 2021). The reported success rate is approximately 70%, although a comparison between studies is not possible due to the many differences in the diagnosis and the analysis of the results (Cabral et al, 2020).…”
Section: Oral Mucosa Applied For Corneal Epithelial Regeneration In Lscdmentioning
confidence: 99%
See 2 more Smart Citations
“…These procedures were named "cultivated oral mucosa epithelial transplantation" (COMET) and "cultivated autologous oral mucosal epithelial cell sheet" (CAOMECS) (Burillon et al, 2012), and they have been widely used in the last 20 years in at least 27 published clinical studies (Attico et al, 2021). The reported success rate is approximately 70%, although a comparison between studies is not possible due to the many differences in the diagnosis and the analysis of the results (Cabral et al, 2020).…”
Section: Oral Mucosa Applied For Corneal Epithelial Regeneration In Lscdmentioning
confidence: 99%
“…Indeed, discrepancies were found in LSCD diagnosis and the inclusion criteria of patients affected by different pathologies, making it difficult to understand the impact of treatment on the ailment (Utheim et al, 2016;Cabral et al, 2020;Attico et al, 2021). Moreover, for autologous limbal cells, many different substrates and culture methods have been used for graft preparation.…”
Section: Oral Mucosa Applied For Corneal Epithelial Regeneration In Lscdmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review of 24 publications between 2004 and 2019 [ 55 ], the authors concluded that COMET is the most frequently used non-limbal autologous cell procedure in the treatment of bilateral LSCD, possibly because it eliminates the risk of graft rejection and thus avoids the need for immunosuppression. The COMET approach has been preferentially performed in Japan, and based on published cases from the last 15 years, they offer promising mid-term results with a stable ocular surface reported in 70.8% of LSCD eyes [ 55 ]. However, neo-angiogenesis following transplantation is a drawback associated with this procedure, but solutions for this problem have been proposed.…”
Section: The Present: Available Stem Cell-based Therapiesmentioning
confidence: 99%
“…For that reason, other cell sources have been sought. Up to now, oral mucosa epithelial cells and MSCs are the only non-limbal epithelial cells that have been proven to be safe and effective for treating patients with ocular surface failure due LSCD [ 55 , 89 ]. Nevertheless, during the last few years, other alternative sources of non-limbal cells have also been investigated in experimental studies with different degrees of success [ 34 , 170 , 171 , 172 ] ( Figure 6 ).…”
Section: The Future: Challenges To Overcome In Stem Cell-based Therapiesmentioning
confidence: 99%